Safety Planning to Manage Suicide Risk with Older Adults: Case Examples and Recommendations. Issue 1 (2nd January 2020) - Conti, Elizabeth C.; Jahn, Danielle R.; Simons, Kelsey V.; Edinboro, Lenis P. Chen; Jacobs, M. Lindsey; Vinson, Latrice; Stahl, Sarah T.; Van Orden, Kimberly A.
ABSTRACT: Adults age 65 and older have high rates of suicide, despite recent efforts to reduce the suicide rate in this population. One suicide prevention strategy with burgeoning empirical support is safety planning; however, there is a lack of information and resources on safety planning for older adults to support uptake of this evidence-based practice in clinical settings where older adults are commonly seen. Safety plans can address risk factors for suicide in older adults, including social isolation, physical illness, functional limitations, and use of highly lethal means. Safety plans also promote relevant protective factors, including increasing use of coping strategies, social support, and help-seeking. Clinicians may encounter challenges and barriers to safety planning with older adults. This paper describes a collaborative, creative approach to safety planning that is relevant and useful for this vulnerable population. Using two case examples, we illustrate how to engage older adults in safety planning, including ways to minimize barriers associated with the aging process.